Sex-Based Differences in Frontal Sinus Anatomy: A Cross-Sectional Study: Sex-Based Differences in Frontal Sinus Anatomy - Imtiaz, Humaira; Khattak, Munila Shabnum; Hayat, Nida Qasim; Jadoon, Omair; Hussain, Atif; Shaheen, Sadaf (Pakistan Journal of Health Sciences, 2024)
Within the frontal bone of the skull, directly above the eyebrows and behind the forehead, lies an air-filled chamber known as the frontal sinus. Objectives: To investigate sex-based differences in frontal sinus anatomy, including measurements such as height, width, and area. Method: This cross-sectional study was conducted at the Department of Anatomy, Women Medical and Dental College, Abbottabad from January 2023 to December 2023. A total of 300 participants were (N = 300). The participants were divided into two groups: 160 men and 140 women. The participants were physically examined using a radiological process. Results: The female and male mean age of 35.2 ± 18.5 years. The right and left side areas of the frontal sinus were significantly higher in males 77.7% and 82.8%, respectively; p = 0.0001) than in females. Males had a significantly greater height (73.3%) and 75.9 % (p = 0.0001) than females on both sides. It was shown that the right and left side widths in males 79.6% and 74.4% significantly higher, p = 0.0001 as compared to females. Males had more supra agger frontal cells and supraorbital ethmoid cells (78.1% and 81.2%, respectively; p < 0.0001). Conclusions: It was concluded that males have larger frontal sinuses in terms of height, width, area, and ethmoid air cell count than females. These results indicate that males have larger and more developed frontal sinuses than females.